FROM AND AFTER 1990: ON LITHUANIAN MENTALITY AND MODERNIZATION - Marius Povilas Povilas Šaulauskas (Problemos)
The article is brought to bear on the political and cultural implications of radical communist modernization to the emerging democracy in post-revolutionary Lithuania as well as in postcommunist world on the whole. First, soviet industrial totalitarianism was not pieced together as a deviation from the western model of modernization, but, conversely, it represents the most violent enhancement of the latter. Second, an endemic specialty of contemporary ex-communist society amounts to the TURBO-modernizing legacy of communist regimes. Although such leftover impedes the consolidation of stable liberal democracy interfering with the disclosure of the Political, nevertheless it also helps to lessen the burden of the unprecedented massive transformations by mitigating pernicious outbursts of ANOMIA. As a result, the conceptual pith of TURBO-modernization – its LOGICALITY – IPSO FACTO contributes to the ongoing deconstruction of communist habitat. Third, in contrast to the third world intellectuals, old communist INTELLIGENTSIA turns out to be critical actor in slackening the grip of ANOMIA and therefore is affected it the least.